2002
DOI: 10.1007/bf02493350
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods for pharmacokinetic screening in rats using LC-MS-MS

Abstract: SummaryThe influence of sample preparation on ion suppression is studied using the model compounds ropivacaine and 3OH-ropivacaine. Three sample preparation techniques are assessed: Solid Phase Extraction (SPE), Direct Dilution and Protein Precipitation.Although requiring more method development and being more time-consuming than the k, vo alternative preparation techniques, SPE had a greater impact on reducing ion suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Grey et al (49) evaluated alkyl-silica sorbents, mixed mode, and polymeric phases in both conventional and multilayer cartridge formats for the determination of paraquat and diquat in environmental waters and vegetables. Mueller et al (50) investigated the effects of mixed-mode SPE and protein precipitation on ion suppression during subsequent electrospray ionization MS, as did Briem et al (51). Both groups found that SPE had a greater impact on reducing ion suppression.…”
Section: Sorptive Extractionsmentioning
confidence: 99%
“…Grey et al (49) evaluated alkyl-silica sorbents, mixed mode, and polymeric phases in both conventional and multilayer cartridge formats for the determination of paraquat and diquat in environmental waters and vegetables. Mueller et al (50) investigated the effects of mixed-mode SPE and protein precipitation on ion suppression during subsequent electrospray ionization MS, as did Briem et al (51). Both groups found that SPE had a greater impact on reducing ion suppression.…”
Section: Sorptive Extractionsmentioning
confidence: 99%